Monitoring of vegetation near power lines based on dynamic programming using satellite stereo images - Qayyum A.; Malik A.S.; Mohamad Saad M.N.; Iqbal M.; Ahmad R.F.; Tuan Abdullah T.A.R.B.; Ramli A.Q. (Institute of Electrical and Electronics Engineers Inc., 2023)
Vegetation encroachment of high voltage power line endorsement space is an exceeding problem for electricity distribution companies. The electrical utilities have responsibility to impose their vegetation management proceeding so as to evade vegetation/ trees near transmission power lines. When the height of trees/vegetation is increased and it makes a contact with the power lines, it may antecedent the power lines in result of blackouts. Blackouts come about due to vegetation encroachments can cause impressive compensation. The uninterrupted electric supply is very imperative for industries, businesses, and populous areas. It is indispensable for electricity companies to monitor the vegetation/trees near power lines, There are many approaches applicable to monitor vegetation/trees near the transmission line poles, but these approaches are time inefficient in terms of time and finance. In this paper, a novel technique for depth estimation of vegetation/trees is proposed. In the study, Dynamic Programming is employed on stereo satellite images to determine depth of vegetation and trees. The experimental results on QuickBird imagery exhibit that the proposed technique performs better compared to block matching technique in terms of accuracy. 2014 IEEE.